(3YeOI GdcJGH hYOI Phj GdCdHGH aj UfGYI GdCbdGe hGdMHQ hGdJPgjH hGdCUHGZs - (3GdeYR Hf HGOjS Hf GdefUhQ GdUfgGLj , J (B454 (3g` s ((3eMeO Hf HgGA GdOjf GdQjSWj s)
(3ChdgG (B:s
(3jHOC HGdHGH GdChd aj aVd Gdbde hGdNW s
(3BNQgG (B:s
(3hGdJejjR hWghQjI GdeGA hEf cGf ef s
(3HChdg Jedcs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG CQVg s
Keywords: (3GdeYGQa GdYGeIs